Evaluation Of Electronic Medical Record (EMR) Implementation At Melai Health Center - Andini, Putri; Ahmad Amiruddin; Selvi Mayang Sari (International Journal of Multidisciplinary Learners, 2024)
The implementation of electronic medical records has seen significant growth in Indonesian healthcare facilities. This is further reinforced by Minister of Health Regulation No. 24 of 2022, which mandates the use of electronic medical records (RME) in all healthcare services. The success of RME implementation is closely tied to the practices of RME users and the organization's management in actively supporting its adoption, which plays a crucial role in determining whether RME is effectively integrated into the organization. This study aimed to examine the implementation of e-puskesmas at the Melai Health Center. Qualitative research method with case study design. Data collection methods were carried out through observation and interviews with two research informants, using interview guideline tools. The results of the study in its implementation have used epuskesmas seen from the aspect of organizational work culture using a collaboration system among officers, the aspect of human resources does not yet have medical record officers with a medical record education background and 4 health center officers have attended RME training, the aspect of health center leadership governance does not yet have SOPs regarding medical record activities and aspects of IT infrastructure, namely the availability of facilities and infrastructure is still lacking such as computers and unstable wifi networks that hinder the RME input process. The suggestion is the addition of several units of computers and printers, the addition of wifi with a stronger network capacity if later.